PEMBENTUKAN PUSAT PENGELOLAAN SAMPAH RUMAH TANGGA: BANK SAMPAH ORGANIK DI DESA SIJERUK - Zulfaidah Ariany (Sekolah Vokasi Universitas Diponegoro, 2025)
The Tri Dharma of Higher Education includes education, research and community service. In order to fulfil these obligations, Diponegoro University is implementing a community service program in Sijeruk Village. This program aims to increase public awareness of organic waste management, which so far has not been managed well. This activity includes counselling, demonstrations and training regarding organic waste management, including the formation of a Waste Bank. Through this program, it is hoped that the community can apply the knowledge gained to overcome waste problems in their environment, thereby creating a cleaner and healthier environment. The results of this activity show that people are starting to understand the importance of good and sustainable waste management.